Risk Factors for Predicting Hypoxia in Adult Patients Undergoing Bronchoscopy under Sedation - Ji Soo Choi; Eun Hye Lee; Sang Hoon Lee; Ah Young Leem; Kyung Soo Chung; Song Yee Kim; Ji Ye Jung; Young Ae Kang; Moo Suk Park; Joon Chang; Young Sam Kim (Tuberculosis and Respiratory Diseases, 2020)
Background Flexible bronchoscopy is one of the essential procedures for the diagnosis and treatment of pulmonary diseases. The purpose of this study was to identify the risk factors associated with the occurrence of hypoxia in adults undergoing flexible bronchoscopy under sedation. Methods We retrospectively analyzed 2,520 patients who underwent flexible bronchoscopy under sedation at our tertiary care university hospital in South Korea January 1, 2013–December 31, 2014. Hypoxia was defined as more than 5%-point reduction in the baseline percutaneous oxygen saturation (SpO2) or SpO2 <90% for >1 minute during the procedure. Results The mean age was 64.7±13.5, and 565 patients developed hypoxia during the procedure. The mean sedation duration and midazolam dose for sedation were 31.1 minutes and 3.9 mg, respectively. The bivariate analysis showed that older age, a low forced expiratory volume in one second (FEV1), use of endobronchial ultrasound, the duration of sedation, and the midazolam dose were associated with the occurrence of hypoxia during the procedure, while the multivariate analysis found that age >60 (odds ratio [OR], 1.32), a low FEV1 (OR, 0.99), and a longer duration of sedation (>40 minutes; OR, 1.33) were significant risk factors. Conclusion The findings suggest that patients older than age 60 and those with a low FEV1 tend to develop hypoxia during the bronchoscopy under sedation. Also, longer duration of sedation (>40 minutes) was a significant risk factor for hypoxia.